2021
DOI: 10.21203/rs.3.rs-281496/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Role of ERBB4 Mutations in the Prognosis of Advanced Non-small Cell Lung Cancer Treated With Immune Checkpoint Inhibitors

Abstract: Introduction: Recently, immune checkpoint inhibitors (ICIs) has been reported to achieved convincing clinical benefits and significantly prolonged the overall survival (OS) of advanced non-small cell lung cancer (NSCLC) patients. Sensitivity to immunotherapy was related to several biomarkers, such as PD-L1 expression, TMB level, MSI-H and MMR. However, novel biomarkers for the prognosis to ICIs treatment need to be further investigated, and it is an urgent demand to establish a systematic hazard model to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…Currently, there is still lack of de nite biomarker in predicting the responses to immunotherapies. Applications of TMB and MSI could partially predict the possible e ciency of anti-PD1/PD-L1 [29,30]. Here we found that CPNE8 expression was negatively correlated with TMB and MSI status in STAD.CPNE8 expression was positively correlated with TMB in HNSC, and negatively correlated with TMB in THCA.…”
Section: Discussionmentioning
confidence: 62%
“…Currently, there is still lack of de nite biomarker in predicting the responses to immunotherapies. Applications of TMB and MSI could partially predict the possible e ciency of anti-PD1/PD-L1 [29,30]. Here we found that CPNE8 expression was negatively correlated with TMB and MSI status in STAD.CPNE8 expression was positively correlated with TMB in HNSC, and negatively correlated with TMB in THCA.…”
Section: Discussionmentioning
confidence: 62%